Improving Scalability with the Use of the Overlay Multicast Protocol (OMP). (6th October 2009) - Al-Misbahi, Hind O.; Al-Aama, Arwa Y.
Demands to increase network usage efficiency and scalability do exist. IP and overlay multicast provide multicasting services by enabling data to be sent to several recipients simultaneously over a network. Although MPLS, a high performance method for forwarding packets, has many benefits, implementation of multicast on MPLS still suffers from IP multicast limitations. This paper proposes the Overlay Multicast Protocol (OMP) in which the overlay approach is applied on MPLS networks to improve the scalability of multicasting. Comparisons of OMP with Protocol Independent Multicast-Sparse Mode and Protocol Independent Multicast-Source Specific Multicast are presented, showing improved scalability when using OMP.